Evaluation Of Job Performance In The Civil Service Sector At Sultanate Of Oman And Its Relations To Job Satisfaction: Descriptive Study - Abdullah bin Salim bin Khalfan Al Hinai; Dr. Salah Mohamed Zaki Ibrahim (OCERINT International, 2024)
Non-Indexed Publication